Idiopathic retroperitoneal haematoma causing duodenal obstruction: a case report and review of literature - Merali, N (Ann R Coll Surg Engl, 2020)
Idiopathic retroperitoneal haematoma is a rare clinical entity; resulting duodenal obstruction is even more occult. It can pose a diagnostic challenge due to variable presentations. Timely management requires a high index of suspicion and a multidisciplinary approach. Surgery is indicated in patients refractory to conservative treatment and failure of endoscopic or interventional radiology options. We report an interesting case illustrating the rarity and severity of this condition, with a review of the literature.